Analysis of the Implementation of Strategic Management in Improving the Quality of Education: Case Study of Ibnu Abbas Islamic Boarding School, Tanjungpinang - Satria, Sabrananda; Kurniawaty, Ria (Journal of Educational Review and Cultural Studies, 2024)
This study aims to evaluate the implementation of strategic management in efforts to improve the quality of education at Pesantren Ibnu Abbas Tanjungpinang, using a qualitative descriptive approach. The primary data was obtained from the management of Pesantren Ibnu Abbas Tanjungpinang, while secondary data was gathered from publications and regulations related to the Pesantren. The analysis was conducted through the stages of strategic management, namely strategy formulation, strategy implementation, and strategy evaluation. The results of the study show that, overall, Ibnu Abbas Tanjungpinang Boarding School has applied strategic management to enhance the quality of education. However, several strategic aspects have not yet been fully optimized, such as the lack of in-depth analysis of internal strengths and external opportunities, as well as the weak commitment of some teachers regarding discipline.